THE EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE AND WORK MOTIVATION ON JOB SATISFACTION OF ASN AT BNN ACEH PROVINCE - Rosdiana; Suryani Hardjo; Nina Siti Salmaniah (RADJA PUBLIKA, 2025)
This research is based onThe aim is to determine the influence of transformational leadership style and work motivation on job satisfaction in civil servants inNational Narcotics Agency of Aceh Province. This study uses total sampling in selecting subjects. The subjects in this study were all employees atNational Narcotics Agency of Aceh Provinceas many as 100 people. There are three hypotheses proposed in this study: (1) There is a positive influence between transformational leadership style and job satisfaction, (2) There is a positive influence between work motivation and job satisfaction, (3) There is a positive influence between transformational leadership style and work motivation on job satisfaction. Based on the research results, there is a significant influence between transformational leadership style and job satisfaction. Where the R coefficient is0.381 and p = 0.000. The correlation is significant, meaning that if the transformational leadership style is high, job satisfaction is higher. The determinant coefficient R2 is0.145, meaning that 14.5% of job satisfaction is influenced by transformational leadership style. Based on the results of this study, it can be stated that the proposed hypothesis 1 is accepted. There is a significant influence of work motivation on job satisfaction. Where the R coefficient is 0.237 and p =0.018. The correlation is significant, meaning that if work motivation is high, job satisfaction is higher. The coefficient of determination R2as big as0.056, meaning that 5.6% of job satisfaction is influenced by work motivation. Together, the variables of transformational leadership style and work motivation have a significant influence on job satisfaction. This can be seen from the model summary table where the R coefficient is 0.427 and p = 0.000. This means that together the variable X1and X2 affects the Y variable. Based on the results of this study, the three hypotheses proposed in this study are declared accepted. The determinant coefficient R2 is0.183, meaning that 18.3% of job satisfaction is influenced by transformational leadership style and work motivation. While 81.7% is influenced by other factors that cannot be explained in the regression equation (residual).